The fraction 16/20 is written as 5/8 in simplest form.

True
False

Answers

Answer 1
Answer: 4/5 if you simplify 16/20

Related Questions

how to draw an arrow diagram that relates a number (0to9) to the number of lit segments required to display that number?
Are the functions linear or nonlinear? 1. y = 2x − 9 2. y = −10.2 3. y = 3x2 + 7 4. 3x + 5y = 15
362. Найдите корень уравнения:- 1) 0,4x (5x – 6) + 7,2 = 2x (x + 0,6); 2) x (3x+2)-9 (x²-7x)=6x (10-x); 3) 12 (x³ - 2) -7x (x² − 1) = 5x³ +2x+6.
We already have 60\%60%60, percent of the items on our list, her father says. Anastasia sees 121212 items in the cart. How many grocery items are on the list?
PLEASE HELP I'LL GIVE YOU 23 POINTSTHERE IS A SCREEN SHOT BUT JUST IN CASE YOU CANT ACCESS IT I'LL ADD THIS!In the figure shown, line AB is parallel to line CD.Part A: What is the measure of angle x? Show your work. (5 points)Part B: Explain how you found the measure of angle x by identifying the angle relationships that you used along the transversal. (5 points)AB and CD are parallel lines, and PQ and PR are transversals which intersect AB at P and CD at Q and R. Angle APQ is labeled as 65 degrees, angle QPR is equal to x, angle PRD is equal to 120 degrees.

How to solve 5x-2(3x-7)=20

Answers

Hi ;) !

These is :  5x-2(3x-7)=20
                5x-6x+14= 20
                -x= 20-14
                 -x=6
                  x= -6
5x-2(3x-7)=20
5x-6x+14=20
-1x=6
X=-6

How many solutions does the equation −5a + 5a + 9 = 8 have?None
One
Two
Infinitely many

Answers

Answer:

Option A is correct

None

Step-by-step explanation:

Like terms are those terms which have same variable to the same power.

Given the equation:

-5a+5a+9=8

Combine Like terms;

0+9 = 8

9 = 8      False.

This statement is false for any values of x

therefore, the given equation does not have any solution.

Hello,

Answer A: None
0a+9=8
==>9=8 equation impossible 0 solution

What is the solution to this system of equations x-3y=-2 x+3y=16

Answers

The solution to the system of equations x - 3y = -2 and x + 3y = 16 is x = 7 and y = 3.

Here, we have,

To solve the system of equations:

Equation 1: x - 3y = -2

Equation 2: x + 3y = 16

There are multiple methods to solve this system, such as substitution or elimination.

Here, we'll use the elimination method to eliminate the variable "x":

Add the two equations together:

(x - 3y) + (x + 3y) = -2 + 16

Simplifying, we get:

2x = 14

Divide both sides of the equation by 2:

2x/2 = 14/2

Simplifying further, we have:

x = 7

Now, substitute the value of x into either of the original equations (let's use Equation 1):

x - 3y = -2

Substituting x = 7, we get:

7 - 3y = -2

Solve for y:

Subtract 7 from both sides:

-3y = -2 - 7

-3y = -9

Divide both sides by -3:

y = -9 / -3

y = 3

Therefore, the solution to the system of equations x - 3y = -2 and x + 3y = 16 is x = 7 and y = 3.

To learn more on equation click:

brainly.com/question/14468218

#SPJ6

x- 3y = -2
x + 3y = 16
----------------add
2x = 14
x = 14/2
x = 7

x + 3y = 16
7 + 3y = 16
3y = 16 - 7
3y = 9
y = 9/3
y = 3

solution is : (7,3)

2k + 5 — 7k = 8 + 3

I need someone to help me out with this one please.

Answers

2k + 5 - 7k = 8+3
-5k + 5 = 11
-5k = 6
k= -6/5

Answer:

-1.2

Step-by-step explanation:

2k+5-7k=8+3

2k-7k+5=11

-5k=11-5

-5k=6

-5k/5=6/5

k=-1.2

If h(x)=x-7 and g(x)=x^ which expression is equivalent to (g•h)(5)?A) (5-7)^
B) (5)^-7
C) (5)^ (5-7)
D) (5-7)x^

Answers

Answer:

A (5-7)^

Step-by-step explanation:

We have the next two functions h(x)=x-7 and g(x)=x^. We need to find (g•h) that is equal to g(h(x)) then:

(g•h)=g(h(x))=(x-7)^

Finally in the poin x=5 we have:

(g•h)=g(h(x))=(x-7)^

(g•h)=g(h(5))=(5-7)^

Then the answer is A

Assuming that by ^, you mean ², here's how you do this:
(g•h)(5) means that you need to solve g(h(5)). So, you plug 5 in for x in h(x), then you plug the solution of that in for x in g(x) like so:
h(5)=5-7 \n g(h(5))= (5-7)^(2)

The answer is A. (5-7)
²

Hope this helps!

B(x) = 7x + 3 and h(x) = 9x - 1.
Find (b+h)(x)

Answers

(b+h)(x)=16x+2

Since we all know the theory that shows that a(x)+b(x)=(a+b)(x), we can use that in this problem. Simply simplify the problem and divide it into 2... b(x) plus h(x). This is simple as we already know the values of these variables so just add both and the sum will be the answer to your problem.